Development of Web-based Differentiated Learning Media on Statistics Materials to Train Critical Thinking Skills at SMKN 1 Kraksaan - Asrumi, Annisa Fadli; Fatirul, Ach Noor; Prayitno, Sunyoto Hadi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This study aims to develop website-based differentiated learning media as a means of supporting mathematics learning, especially on statistics material for Vocational High School (SMK) level students. This learning media is designed to suit the various learning styles of students-visual, auditory, and kinesthetic-and to improve critical thinking skills through the integration of information technology and digital media in the learning process. The method used follows the development model (ADDIE) which includes the stages of analysis, design, development, implementation and evaluation, by integrating various types of media, such as ebooks, learning videos, and educational games. The results showed that the media developed averaged 91% expert test and 92.25% peer test, this means that the teaching materials are feasible to be applied to learning activities and are able to provide varied learning experiences and in accordance with the learning characteristics of students, thus having a positive impact on their motivation and critical thinking skills.